'Global mental health': systematic review of the term and its implicit priorities. Issue 3 (May 2019) - Misra, Supriya; Stevenson, Anne; Haroz, Emily E.; de Menil, Victoria; Koenen, Karestan C.
Abstract : Background: The term 'global mental health' came to the fore in 2007, when the Lancet published a series by that name. Aims: To review all peer-reviewed articles using the term 'global mental health' and determine the implicit priorities of scientific literature that self-identifies with this term. Method: We conducted a systematic review to quantify all peer-reviewed articles using the English term 'global mental health' in their text published between 1 January 2007 and 31 December 2016, including by geographic regions and by mental health conditions. Results: A total of 467 articles met criteria. Use of the term 'global mental health' increased from 12 articles in 2007 to 114 articles in 2016. For the 111 empirical studies (23.8% of articles), the majority (78.4%) took place in low- and middle-income countries (LMICs), with the most in Sub-Saharan Africa (28.4%) and South Asia (25.5%) and none from Central Asia. The most commonly studied mental health conditions were depression (29.7%), psychoses (12.6%) and conditions specifically related to stress (12.6%), with fewer studies on epilepsy (2.7%), self-harm and suicide (1.8%) and dementia (0.9%). The majority of studies lacked contextual information, including specific region(s) within countries where studies took place (20.7% missing), specific language(s) in which studies were conducted (36.9% missing), and details on ethnic identities such as ethnicity, caste and/or tribe (79.6% missing) and on socioeconomic status (85.4% missing). Conclusions: Research identifying itself as 'global mental health' has focused predominantly on depression in LMICs and lacked contextual and sociodemographic data that limit interpretation and application of findings. Declaration of interest: None.